Emerging green product buyers in Malaysia: Their profiles and behaviours - Mohd Noor, Nor Azila; Mat, Norsiah; Mat, Norazuwa; Jamaluddin, Che Zuriana; Salleh, Hayatul Safrah; Muhammad, Azli (2012)
Over the past decades, concern about the environment has become not only a significant public issue but also a crucial topic in academic research. Concern about environmental sustainability and climate change has increased dramatically in the past and is affecting the way consumers behave. This change has lead to a greater focus on green consumerism. No doubt that environment is essential for the growth and survival of all living beings. But unfortunately environment has fallen prey for mankind. Nature is being degraded by the activities undertaken by companies. Hence, it becomes the responsibility of the business world to compensate for the harm that the companies are causing to environment. The growing social concern for the environment has recently emerged as a key issue in marketing. In recent years, this fact has leads to an increased interest by consumers in making environmentally social purchases. Recently, green consumerism has started to gradually emerge in the Asian region. With the interest in green consumerism, Asian consumers have recently become one of the primary targets for international marketers. Research has shown that consumers have translated their resulting environmental concern into actively purchasing green products. This study describes the profile of green product buyers in Malaysia. By using mall intercept survey, data were collected from consumers who do shopping at hypermarkets in Malaysia. From the analysis undertaken, it was found that level of green purchase behavior among Malaysian consumers is not encouraging. In this study, green purchase behavior tends to be differ across different gender where females tend to be greener than males. Green buyers do not differ across different level of household income and the green buyers are composed of married respondents. The theoretical implications and managerial implications of these findings are discussed.